Language applied in tourist hotspot in Malaysia: issues and challenges - Abdul Rahim, Abdul Hadi; Mohd Sohime, Nor Afandi; Abdul Rahim Merican, Rooshida Mericn (Kulliyyah of Languages and Management, International Islamic University Malaysia, Pagoh, 2016)
The paper discusses the issues and challenges of English language as a medium of instruction in the tourism industry specifically the hotel business in Malaysia. The main purpose of this paper is to assist the hotel employees in dealing with tourists from all over the world. This paper will examine the problems faced between hotel employees and tourists in relation to the English Language. There is strong possibility that the problem arises due to poor communication skills, bad hospitality service and even grammatical error on travel brochures and signboards. Hence, it is highly recommended that the Malaysian government and the Ministry of Tourism and Culture of Malaysia work together to improve the language skills of the people, particularly the hotel employees.